PENGARUH DISIPLIN KERJA DAN ETOS KERJA SERTA GAYA KEPEMIMPINAN SITUASIONAL TERHADAP KINERJA PEGAWAI DI KANTOR BADAN PENANGGULANGAN BENCANA DAERAH KOTA PALU - Rinaldi, Marsyaf (Katalogis, 2016)
This Research Target is (1) the knowing and analysing discipline influence work, ethos work and style of leadership conditions to officer performance of  office  Body of Solving of Disaster in Palu City. (2) To know and analyse the discipline influence work to officer performance at Body of Solving of Disaster in Palu City. (3) To know and analyse the Ethos influence work to officer performance  at  Body of Solving of Disaster in Palu City. (4) To know and analyse the influence of Style of Leadership conditions to officer performance at Body of Solving of Disaster in Palu City. This Research Type is research cuatitative. Population in this research amount to 36 responder people by using census method.  Result of research menunjukan: (1) Discipline work the, ethos work and style of leadership conditions by simultan have an effect on the significant to officer performance in  Body of Solving of Disaster of Palu City (2) Discipline work by parsial have an effect on the significant to officer performance  Body of Solving of Disaster of Palu City. (3) Ethos work by parsial have an effect on the significant to officer performance in Body of Solving of Disaster of Palu City (4) Style of leadership conditions by parsial do not have an effect on to officer performance in Body of Solving of Disaster of Palu City.